Aramaic and Hebrew inscriptions from Mt. Gerizim and Samaria between Antiochus III and Antiochus IV Epiphanes - Dušek, Jan. (Culture and History of the Ancient Near East, 2012)
The theme of the book stands on the intersection of epigraphy and historical research: the Aramaic and Hebrew inscriptions discovered in the vicinity of the Yahwistic sanctuary on Mt. Gerizim and their historical background. The study addresses the evidence from three perspectives: the paleography and dating of the inscriptions; the identity of the community who carved them and its institutions; and, finally, the larger historical and political context in which the inscriptions were produced. This book is particularly useful for historians of Palestine in the Second Temple period, for biblical scholars, and for those dealing with Aramaic and Hebrew paleography and epigraphy. \'Dušek's book balances skilfully between epigraphy and historical research.\' Alinda Damsma, University College London \'...this book largely succeeds in its aims, providing an impressively erudite, fascinatingly detailed reconstruction of the historical, economic, and social contexts of the inscriptions from Mt. Gerizim.\' Jeremy M. Hutton, University of Wisconsin - Madison